A blogging good time? The use of blogs as a reflective learning and feedback tool for final year public relations students - Wolf, Katharina (WACE - ACEN Asia Pacific Conference, 2008)
This article reflects on the use of web logs (blogs) as an assessable component in a third year professional placement unit for public relations students. The key objective behind the use of Web2.0 technology was to encourage reflective practice via an exchange between students and thereby limit the feeling of isolation during the course of this individual tuition unit (ITU). Secondary objectives were to encourage exchange between participating students based at different, on- and offshore campuses, therefore integrating an international perspective into the practice of public relations. From a unit coordinator perspective an additional objective was to create an opportunity that would aid in the early detection of potential problems and to provide a forum in which additional learning material could be provided in response to arising issues. Both challenges and opportunities are noted in this paper. Overall, the Reflective Blog trial can be described as a success, both from the staff as well as the student perspective. However, the Reflective Blog has its shortcomings, particularly from an administrative perspective. As additional students from offshore locations are slowly phasing in, the sustainability of the Reflective Blog will have to be closely monitored.